Gambaran Nutrisi Lansia Di Desa Banua Baru - Fredy Akbar K; Idawati Ambo Hamsah; Ayuni Muspiati M (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
The elderly is the last phase in human life, where every aged person will definitely pass through this phase. As we age, all organ functions have reached their maximum peak so what is happening now is a decline in organ function. There are many elderly people in Indonesia who experience nutritional fulfillment disorders who experience malnutrition (BMI 16.5-18.49%) as much as 31% and more nutrition 1.8%. Nutrition is less often caused by social and economic problems and also due to disease disorders, if the consumption of calories is too low than needed then the body weight is less than normal. The purpose of this study, to determine the amount of BMI and the type of nutritional intake in the elderly. The research design is quantitative descriptive. The study was conducted by measurements and observations made in one time with the inclusion criteria are the elderly who can be invited to communicate, using a design on the variable Screening Mini Nutritional Assessment (MNA). The results of the study were obtained from 18 samples experiencing malnutrition and 20 samples of risk of experiencing malnutrition, while for the measurement of BMI from the elderly obtained values ​​of 0 = BMI <19; 19 people, value 1 = BMI 19-21; 9 people, value 2 = BMI 21- 23; 6 people, value 3 = BMI> 23; 4 people.